Isbädd topografi och istjocklek DEMS från Greenland Analogue Project (GAP) - Lindbäck, Katrin; Pettersson, Rickard (Swedish National Data Service, 2019)
We present ice thickness and bed topography digital elevation models (DEMs) of a land-terminating section of the Greenland Ice Sheet, based on a compilation of ground-based and airborne radar surveys. The DEMs have a total area of ~12,000 km^2 at a resolution of 250 to 500 m. Our combined dataset of ground-based and airborne radar surveys is available for integration into databases of bed elevation on Greenland and can be valuable for detailed studies of ice sheet dynamics and hydrology. Data acquisition method description: The GAP dataset was compiled from three different sources. Uppsala University collected ground-based radar surveys during spring 2010 and spring 2011 which was combined with two airborne radar datasets, collected by the Technical University of Denmark in 2003 and by the NASA IceBridge project between 2010 and 2012. Information about data and methods are described in: Lindbäck, K., Pettersson, R., Doyle, S. H., Helanow, C., Jansson, P., Kristensen, S. S., … Hubbard, A. L. (2014). High-resolution ice thickness and bed topography of a land-terminating section of the Greenland Ice Sheet. Earth System Science Data, 6(2), 331–338. doi:10.5194/essd-6-331-2014 Vi presenterar digitala höjdmodeller (DEM) för istjocklek och isbäddtopografi av en markavslutande del av Grönlands istäcke baserade på markbaserade och luftburna radarundersökningar. Mer information finns på studiens engelska sida: https://snd.gu.se/en/catalogue/study/ecds0153 Information om data och metoder beskrivs i: Lindbäck, K., Pettersson, R., Doyle, S. H., Helanow, C., Jansson, P., Kristensen, S. S., … Hubbard, A. L. (2014). High-resolution ice thickness and bed topography of a land-terminating section of the Greenland Ice Sheet. Earth System Science Data, 6(2), 331-338. doi:10.5194/essd-6-331-2014